2002
DOI: 10.1034/j.1600-0528.2002.300203.x
|View full text |Cite
|
Sign up to set email alerts
|

Childhood dental fear in the Netherlands: prevalence and normative data

Abstract: The results have shown 6% of the Dutch child population to be highly fearful, while another 8% may be at risk to develop high dental fear. By providing extra attention for these children, the development of high dental fear or phobia may be prevented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
102
4
11

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(150 citation statements)
references
References 27 publications
21
102
4
11
Order By: Relevance
“…The present study showed that mean anxiety score is significantly higher in girls than in boys (p=0.006). Our findings are similar to the findings of Ten Berge M et al (17), Maja L et al (18), Majstorovic et al (19), and Nakai et al (20). Some study had shown no significant difference in mean anxiety score between boys and girls (girl vs. boys mean CFSS-DS was 27.50+/-5.01, and 26.84+/-5.62, respectively) (21).…”
Section: Raspravasupporting
confidence: 81%
See 1 more Smart Citation
“…The present study showed that mean anxiety score is significantly higher in girls than in boys (p=0.006). Our findings are similar to the findings of Ten Berge M et al (17), Maja L et al (18), Majstorovic et al (19), and Nakai et al (20). Some study had shown no significant difference in mean anxiety score between boys and girls (girl vs. boys mean CFSS-DS was 27.50+/-5.01, and 26.84+/-5.62, respectively) (21).…”
Section: Raspravasupporting
confidence: 81%
“…U našem istraživanju srednja vrijednost CFSS-DS-a za dječake bila je 19,23+/-6,30, a za djevojčice 22,17+/-10,72, odnosno srednja vrijednost anksioznosti bila je značajno veća kada je riječ o djevojčicama negoli o dječacima (p = 0,006). Naši su rezultati slični onima Tena Berge i suradnika (17), Maje i suradnika (18), Majstorović i suradnika (19) te Nakaija i suradnika (20). Neka istraživanja nisu pokazala značajnu razliku srednjih vrijednosti ankioznosti između dječaka i djevojčica (srednja vrijednost CFSS-DS-a za djevojčice u odnosu prema dječacima; 27,50+/-5,01 i 26,84+/-5,62, tim redom) (21).…”
Section: Raspravaunclassified
“…It has been shown to have good reliability-validity, and recently has been used in several countries and translated into several languages [10,11] . CFSS-DS is used to register differences in dental fear between experimental and control groups to select fearful and non-fearful children from a larger reference population and to estimate the prevalence of dental fear in children [8,11] . CFSS-DS has been shown to be better in some situations than other scales such as the Venham Picture Test and the Dental Anxiety Scale [12] .…”
mentioning
confidence: 99%
“…Dental korku ve diş çürüğü, birbirleri için hem sebep hem sonuç olabilir (30). Kruger ve arkadaşları (31) dental korkunun çürükler için önemli bir belirleyici olduğunu belirtmişlerdir .…”
Section: Tartiġmaunclassified